2021
DOI: 10.1140/epjp/s13360-021-01872-4
|View full text |Cite
|
Sign up to set email alerts
|

The $$^{27}\hbox {Al}(\hbox {p},\alpha )^{24}\hbox {Mg}$$ reaction at astrophysical energies studied by means of the Trojan Horse Method applied to the $$^2\hbox {H}(^{27}\hbox {Al},\alpha ^{24}\hbox {Mg})\hbox {n}$$ reaction

Abstract: The $$^{27}\hbox {Al}(\hbox {p},\alpha )^{24}\hbox {Mg}$$ 27 Al ( p , α ) 24 Mg reaction, which drives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…As discussed above, the results from Palmerini et al (2021) showed us that no particle identification was necessary using the ΔE-E technique. Instead, we carried out channel identification using the kinematic techniques discussed in, e.g., La Cognata et al (2010).…”
Section: Selection Of the Reaction Channelmentioning
confidence: 91%
See 4 more Smart Citations
“…As discussed above, the results from Palmerini et al (2021) showed us that no particle identification was necessary using the ΔE-E technique. Instead, we carried out channel identification using the kinematic techniques discussed in, e.g., La Cognata et al (2010).…”
Section: Selection Of the Reaction Channelmentioning
confidence: 91%
“…The beam energy was chosen to span the 27 Al−p energy range between the threshold and ∼1.5 MeV for normalization to measured resonance strengths. In this work, a higher beam energy than in the previous run (see Palmerini et al 2021 for details) was considered to explore a phase-space region where the contribution of the 25 Mg compound-nucleus decay to the reaction yield is negligible.…”
Section: The Experimental Approachmentioning
confidence: 99%
See 3 more Smart Citations